303 OXIDATION OF THE THIOL DISULFIDE CYSTEINE/CYSTINE REDOX COUPLE STIMULATES LUNG FIBROBLAST PROLIFERATION AND MATRIX EXPRESSION THROUGH REDOX SIGNALING. (1st January 2006) - Ramadan, B.; Ritzenthaler, J. D.; Rivera, H.; Roser-Page, S.; Jones, D.; Roman, J.
Abstract : Oxidant stress has been implicated in the pathogenesis of chronic fibrosing lung disorders like idiopathic pulmonary fibrosis, and environmental and host factors capable of causing chronic oxidant stress have been identified. However, the mechanisms that link oxidant stress to fibrogenesis remain only partially elucidated. We hypothesize that extracellular oxidant stress affects lung fibroblasts directly by inducing intracellular pathways (ie, redox signaling) that stimulate their proliferation and matrix expression. In experiments designed to test this hypothesis, we showed that extracellular oxidant stress caused by oxidation of the thiol disulfide cysteine (Cys)/cystine (CySS) redox couple stimulates lung fibroblast proliferation. This is intriguing because most of the available research on oxidant stress has focused on intracellular oxidant stress and glutathione, the most abundant low-molecular-weight thiol in cells. However, evidence suggests that the extracellular thiol/disulfide redox environment may also be important. The Cys/CySS redox couple represents the predominant low-molecular-weight thiol/disulfide pool found in plasma, and it is sensitive to many host factors (eg, aging and smoking). Further work revealed that lung fibroblasts cultured in the setting of oxidized extracellular Cys/CySS redox (246 mV) showed increased expression of fibronectin, a matrix glycoprotein highly expressed in fibrotic lung disease and implicated in lung injury and repair. This stimulatory effect was related to increased fibronectin gene transcription, was enhanced by nicotine, and was blocked by inhibitors of protein kinase C activation. Fibroblasts cultured on normal medium (280 mV) or reduced medium (2130) medium showed no induction. Lung fibroblasts cultured in oxidized extracellular Cys/CySS redox also showed phosphorylation of CREB, a transcription factor known for its ability to stimulate fibronectin expression. Other transcription factors stimulated were NFkB and Smad3. Together, these studies suggest that extracellular oxidant stress, through oxidation of the thiol/disulfide couple Cys/CySS, activates redox-sensitive pathways that stimulate the differential expression of genes that enhance fibroblast proliferation and matrix deposition.